La violenza tra tradizione e digital society Una riflessione sociologica - Sannella, Alessandra (Open Sociology - Open access, 2017)
"The text explores the phenomenon of violence, retracing the sociological theory from the classical paradigms to the frontier of interpretative readings outlined in the digital society age. The aim is to arrive at an interpretation on violence and the possible connections that go from traditional society, in the historiographic sense of action, to the challenges proposed by contemporary society. What is the form that violence takes today? Which are the indicators that allow you to recognize it? Following these reflections, this book raises the question about the social nature of violence in the many forms in which it manifests itself. The analysis that is proposed is therefore that of seeking the widespread dimensions within which the contemporary individual acts, as well as identifying the indicators that, through functional categories, can prevent and combat violence."